Sulfhemoglobinemia and methemoglobinemia following acetaminophen overdose. (2022) - Seltzer, Justin A.; Bubic, Irvan; Winkler, Garret A.; Friedman, Nathan A.; Bagby, Jessica; Tomaszewski, Christian A.; Clark, Richard F.; Kreshak, Allyson; Lasoff, Daniel R.
Abstract: Introduction: Though acetaminophen overdoses are common, acetaminophen induced methemoglobinemia is rare and it is thought to be due to oxidative stress from reactive metabolites. However, few prior cases of sulfhemoglobinemia in the setting of acetaminophen overdose have been reported. We report a case of mixed methemoglobinemia and sulfhemoglobinemia in the setting of a large, isolated acetaminophen ingestion. Case report: A 30-year-old African American male presented after intentionally ingesting 50 tablets of 500 mg acetaminophen two days prior. He was cyanotic and tachypneic. Peripheral oxygen saturation was 78 % on room air and minimally improved with high-flow oxygen. He was noted to have leukocytosis, thrombocytopenia, anion gap metabolic acidosis with lactic acidemia, acute kidney injury, transaminitis, hyperbilirubinemia, and coagulopathy. Arterial partial pressure of oxygen was normal. Methemoglobin and sulfhemoglobin concentrations were 8.5 % and 5.2 %, respectively. Along with intravenous N-acetylcysteine, methylene blue was administered without clinical improvement. Hemolytic anemia was subsequently noted. Glucose-6- phosphate dehydrogenase (G6PD) deficiency was then confirmed with a quantitative assay and genetic testing. He also received one dose of intravenous metoclopramide. The patient ultimately required eight units of packed red blood cells and several weeks of hemodialysis before discharge on hospital day 43. Discussion: Acetaminophen is structurally related to compounds known to cause methemoglobinemia and sulfhemoglobinemia. We hypothesize that these dyshemoglobinemias were triggered by acetaminophen-induced oxidative stress. The role of G6PD deficiency in the formation of sulfhemoglobinemia is unclear. Acetaminophen overdoses presenting with methemoglobinemia should prompt concern for underlying G6PD deficiency. Coincidental sulfhemoglobinemia should be considered if the clinical presentation is more severe than the methemoglobin concentration alone would suggest. Use of methylene blue in this case, despite the low measured methemoglobin percentage, which likely triggered hemolytic anemia; methylene blue use in a similar circumstance should be weighed carefully against the risk of harm Graphical Abstract: ga1 Highlights: Acetaminophen induced methemoglobinemia is rare and it is thought to be due to oxidative stress from reactive metabolites. Sulfhemoglobinemia following acetaminophen overdose has not been reported previously but is possible due to oxidative stress in the setting of G6PD deficiency. Acetaminophen overdoses with methemoglobinemia should prompt concern for G6PD deficiency and coincidetal sulfhemoglobinemia; caution should be exercised in this setting given the risk of hemolysis with oxidizing medications such as methylene blue.